Kingdom of the Netherlands : Netherlands; Report on the Observance of Standards and Codes; Data Module, Response by the Authorities, and Detailed Assessment Using the Data Quality Assessment Framework (DQAF). - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Dutch macroeconomic statistics are generally in accordance with internationally accepted standards and guidelines on concepts and definitions, scope, classification and sectorization, and basis for recording. They are also available with periodicity and timeliness that always meet, and sometimes exceed, Special Data Dissemination Standard (SDDS) requirements. The macroeconomic statistics of the Netherlands get high marks for accuracy and reliability. The range of annual source data for national accounts is extensive. However, there are no quarterly collections from enterprises for gross fixed capital formation or inventories.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet